Weighing and prioritization of individual factors affecting the performance of industries firefighters. (January 2022) - Heydari, Payam; Babamiri, Mohammad; Tapak, Leili; Golmohammadi, Rostam; Kalatpour, Omid
Abstract: The proper functioning of emergency response team members is crucial for the success of any emergency response operation. The present study was designed to weigh and prioritize the personal factors that shape the performance of industrial firefighters. Accordingly, the published articles in scientific databases were searched. Initially, 262 articles were identified. After excluding the duplicate articles, 44 eligible articles from 2000 to 2021 were selected. The identified factors were categorized into three cognitive, physical, and psychological factors. In the next step, the opinions of 10 experts were used to prioritize the most relevant factors (criteria and sub-criteria) shaping the performance. Then, the criteria and sub-criteria were compared by DEMATEL technique to remove the factors of lower importance, and finally were weighted and prioritized by the ANP technique. Situation awareness, risk perception, and attention were identified as the most important cognitive factors. The most important physical shaping factors were fatigue/pain, chronic health disorders, and musculoskeletal disorders. Conscientiousness, job stress, and resilience were the most important psychological shaping factors. It is necessary to evaluate the firefighters' performance. Due to the influential role of situation awareness, fatigue/pain, and conscientiousness on firefighters' performance, these critical factors should be reinforced to promote the firefighters' performance. Highlights: Extraction of the general performance shaping factors (PSF). Grouping the factors that can shape performance of firefighters. Comparison of criteria using DEMATEL technique. Weighting and prioritizing the criteria and sub-criteria using ANP technique.